2013
DOI: 10.1098/rspb.2013.2025
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable, efficient livestock production with high biodiversity and good welfare for animals

Abstract: What is the future for livestock agriculture in the world? Consumers have concerns about sustainability but many widely used livestock production methods do not satisfy consumers' requirements for a sustainable system. However, production can be sustainable, occurring in environments that: supply the needs of the animals resulting in good welfare, allow coexistence with a wide diversity of organisms native to the area, minimize carbon footprint and provide a fair lifestyle for the people working there. Conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
186
2
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(204 citation statements)
references
References 44 publications
(64 reference statements)
2
186
2
14
Order By: Relevance
“…Grazing is often considered the most sustainable way of producing milk, owing to lower production costs, higher quality products and greater social acceptance (Broom et al, 2013). In many parts of the world, pasture-based systems are synonymous with compact seasonal calving to match feed demand and pasture growth.…”
Section: Introductionmentioning
confidence: 99%
“…Grazing is often considered the most sustainable way of producing milk, owing to lower production costs, higher quality products and greater social acceptance (Broom et al, 2013). In many parts of the world, pasture-based systems are synonymous with compact seasonal calving to match feed demand and pasture growth.…”
Section: Introductionmentioning
confidence: 99%
“…This definition stresses the importance of good health and animal needs (either physical or emotional) to achieve good standards of welfare. Animal welfare is considered to be a necessary element of sustainable animal production (Broom et al, 2013). Increasingly, society demands that animal welfare be integrated into the concept of sustainable livestock production (Appleby, 2005).…”
Section: Contribution Of Livestock To Global Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Increasingly, society demands that animal welfare be integrated into the concept of sustainable livestock production (Appleby, 2005). A growing number of consumers demand ethical production systems and refuse to buy products if they are produced under morally unacceptable circumstances (Broom et al, 2013). For example, Clonan et al (2015) found that welfare is a choice criterion for 88% of surveyed consumers when buying any meat.…”
Section: Contribution Of Livestock To Global Greenhouse Gas Emissionsmentioning
confidence: 99%
“…The most important animals for food production are those that eat food that humans cannot eat. Hence, herbivores eating forage plants, not cereals, are much more important than pigs or poultry, which compete with humans for food (Broom et al, 2013). Similarly, herbivorous fish are more important than those fish that eat other fish.…”
Section: Efficient Use Of World Resourcesmentioning
confidence: 99%
“…Livestock production can also result in pollution, locally and on a world-wide scale, e.g., via greenhouse gas production. Greenhouse gas production should be reduced and may have to be balanced against efficiency of use of world resources (Broom et al, 2013).…”
Section: Harmful Environmental Effectsmentioning
confidence: 99%